HLA‐C*06:103, a novel allele was identified in a Chinese patient awaiting hematopoietic stem cell transplantation. Issue 6 (6th March 2015) - Han, Z.‐D.; He, J.; Wang, W.; Zhu, F.‐M.; Lv, H.‐J.
<x xml:space="preserve">Abstract</x> HLA‐C*06:103 shows four nucleotides difference from that of HLA‐C*06:02:01:01.